Inhibition of Bacterial Neuraminidase and Biofilm Formation by Ugonins Isolated From Helminthostachys Zeylanica (L.) Hook - Shah, Abdul Bari; Baiseitova, Aizhamal; Kim, Jeong Ho; Lee, Yong Hyun; Park, Ki Hun (Frontiers in Pharmacology, 2022)
Bacterial neuraminidase (BNA) plays a pivotal role in the pathogenesis of several microbial diseases including biofilm formation. The aim of this study is to reveal the neuraminidase inhibitory potential of metabolites from Helminthostachys zeylanica (L.) Hook. which have diverse biological activities including PTP1B and α-glucosidase. The six ugonins (1-6) from the target plant showed significant neuraminidase inhibition. The inhibitory potencies were observed at a nanomolar level of 3550 nM, which means they are 100 times more active than their corresponding mother compounds (eriodyctiol and luteolin). A detailed kinetic study revealed that all ugonins were reversible noncompetitive inhibitors. An in-depth investigation of the most potent compound 1 showed its time-dependent inhibition with the isomerization model having k5 = 0.0103 min-1, k6 = 0.0486 min-1, and Ki app = 0.062 μM. The binding affinities (Ksv) were agreed closely with our prediction based on the inhibitory potencies. Particularly, ugonin J (1) blocked the biofilm formation of E. coli dose-dependently up to 150 µM without the inhibition of bacteria. The major compounds (1-6) in the extract were characterized by UPLC-ESI-Q-TOF/MS.